Ubiquitin-modifying enzymes in thyroid cancer：Mechanisms and functions - Xingmin Xiong; BenBen Huang; Zhe Gan; Weixiang Liu; Yang Xie; Jianing Zhong; Xiangtai Zeng (Heliyon, 2024)
Thyroid cancer is the most common malignant tumor of the endocrine system, and evidence suggests that post-translational modifications (PTMs) and epigenetic alterations play an important role in its development. Recently, there has been increasing evidence linking dysregulation of ubiquitinating enzymes and deubiquitinases with thyroid cancer. This review aims to summarize our current understanding of the role of ubiquitination-modifying enzymes in thyroid cancer, including their regulation of oncogenic pathways and oncogenic proteins. The role of ubiquitination-modifying enzymes in thyroid cancer development and progression requires further study, which will provide new insights into thyroid cancer prevention, treatment and the development of novel agents.